2019
DOI: 10.1007/s12197-019-09471-x
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of policy uncertainty on stock prices

Abstract: A new measure of policy uncertainty that relies upon newspapers' reporting of any words that contribute to an uncertain environment is constructed and published by Policy Uncertainty Group. In this paper we assess its impact on stock prices in 13 countries for which we were able to locate the required data. We find that in almost all 13 countries, increased uncertainty has adverse short-run effects but not long-run effects on stock prices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…ese policy uncertainties have a significant impact on financial markets and a growing interest in the literature relating to the link between EPU and international financial markets, most especially the stock markets, which have led several researchers to focus on this area. us, studies by Brogaard and Detzel [37], Arouri et al [38], Bahmani-Oskooee and Saha [12], Adam [39], Asafo-Adjei et al [40], and Chiang [41] have demonstrated that heightened uncertainty hurts stock returns. Moreover, Pastor and Veronesi [42], Liu and Zhang [43], Tsai [44], and Jurado et al [19] with different research orientations focus on the impact of uncertainty on stock market volatility and find that the inclusion of EPU can enhance the predictability of stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…ese policy uncertainties have a significant impact on financial markets and a growing interest in the literature relating to the link between EPU and international financial markets, most especially the stock markets, which have led several researchers to focus on this area. us, studies by Brogaard and Detzel [37], Arouri et al [38], Bahmani-Oskooee and Saha [12], Adam [39], Asafo-Adjei et al [40], and Chiang [41] have demonstrated that heightened uncertainty hurts stock returns. Moreover, Pastor and Veronesi [42], Liu and Zhang [43], Tsai [44], and Jurado et al [19] with different research orientations focus on the impact of uncertainty on stock market volatility and find that the inclusion of EPU can enhance the predictability of stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e null hypothesis of unit root, H 0 : θ � 0, is tested against the nonlinear ESTAR process, H 1 > 0, in equation (12). Because according to Kapetanios et al [67] the null hypothesis cannot be directly tested, a reparameterization of equation ( 12) is suggested by computing a first-order Taylor series approximation to obtain auxiliary regression equation given by…”
Section: Testing For Nonlinear Characteristics Of the Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in the context of the US, the phenomena are also captured by a few studies [14,[21][22][23]27] with conflicting findings. For example, some of them [14,15,21,23,34] found a negative relationship, while others reported no effect [22,27]. The conflicting referred literature on the US [14,15] relies on the classical approach [35] to capture the cointegration relationship.…”
mentioning
confidence: 99%
“…For example, some of them [14,15,21,23,34] found a negative relationship, while others reported no effect [22,27]. The conflicting referred literature on the US [14,15] relies on the classical approach [35] to capture the cointegration relationship. From the symmetry assumption perspective drawn on this approach [35], it follows that an increase in PU will negatively affect the other macroeconomic variables and that a decrease in PU will increase this variable.…”
mentioning
confidence: 99%